MORPHOMETRY OF THE MANDIBLE AND UPPER JAW OF THE NATIVE DOGS OF TIRUNELVELI DISTRICT AND ITS CLINICAL VALUE DURING REGIONAL ANAESTHESIA - S. Rajathi; S. Muthukrishnan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The aim of the study was to get information on the morphometric measurements of the upper jaws and mandibles of native dogs of Tirunelveli district and its clinical value during regional anaesthesia. The study was undertaken on six upper jaws and mandibles of adult dogs without any apparent skeletal disorders. A total of 17 measurements and data were recorded. The skull length, cranial length, nasal length and cranial width were 18.2 ± 0.21 cm, 10.7 ± 0.35 cm, 7.5 ± 0.02 cm and 7.0 ± 0.56 cm respectively. In addition, the distance from the root of the premolar tooth to the infraorbital canal and from the latter to the root of the canine tooth was 0.9 ± 0.85 cm and 2.8 ± 0.44 cm, respectively. The length and height of the mandible were 12.8 ± 0.12 cm and 6.1 ± 0.55 cm, respectively. The distances from the lateral alveolar root to the mental foramen and from the mental foramen to the caudal mandibular border were 2.0 ± 0.66 cm and 10.5 ± 0.89 cm, respectively. The distances from the mandibular foramen to the base of the mandible as well as from the caudal border of the mandible to below of the mandibular foramen were 1.1 ± 0.75 cm and 1.4 ± 0.33 cm, respectively. Also the distances from the base of the mandible to the condyloid fossa and from the latter to the maximum height of the mandible were 3.4 ± 0.88 cm and 2.6 ± 0.05 cm, respectively. The distances from the caudal border of the mandible to the mandibular foramen and from the latter to the mandibular angle were 1.5 ± 0.21 cm and 1.1 ± 0.66 cm respectively. These data were important landmarks with regard to their application to clinical maneuvers around the head of the native adult dogs such as regional anaesthesia during treating head injuries and dental extraction.